Emilia Pardo Bazán as a Model in the Contemporary Galician Narrative (1899- 1919) - Rodríguez González, Olivia (Madrygal. Revista de Estudios Gallegos, 2021)
Regarding the question of whether Emilia Pardo Bazán’s work and thought were assimilated or rejected by the Galician literary protosystem, this paper attempts to answer by showing how, throughout her life and creative career (1851-1921), the author was taken into account, even as a canonical reference, at difficult times for the Galician narrative protosystems during the late 19th century and the first decades of the 20th century. Those were also decisive times for the continuation of the Rexurdentist path in the first case; and in the other, for the formation of the second renaissance towards the definitive modern Galician narrative of the 20th century. Two novels, by «Xan de Masma» (pseudonym of Patricio Delgado Luaces) and by Vicente Risco, are focused here, within the framework of Iberian comparatism, from two titles by Pardo Bazán, Los Pazos de Ulloa and La sirena negra. Thematological and metaliterary evidence is adduced, as well as evidence of affiliation to certain schools or aesthetics, etc., in order to conclude that there were systemic transfers that originated from the position that Emilia Pardo Bazán occupied in the Parnassus of writers who were forging that narrative in Galician.